Gypsum Biomineralization in Sulphide-rich Hardpans by a Native Trichoderma harzianum Rifai Strain. Issue 3 (16th March 2018) - Cecchi, Grazia; Marescotti, Pietro; Di Piazza, Simone; Lucchetti, Gabriella; Mariotti, Mauro Giorgio; Zotti, Mirca
ABSTRACT: Natural acid mine drainage affects abandoned sulfide mines worldwide, causing hardpan formation and heavy metal leaching. Hardpans are characterized by very low permeability, thus representing a significant limiting factor for oxygen and water circulation in the rhizosphere. Our work shows the results concerning the gypsum biomineralization capability of a native Trichoderma harzianum Rifai strain in sulfide -rich hardpans. Two months after the fungal inoculum, hardpan clasts resulted, completely covered by T. harzianum mycelium, where newly formed gypsum crystals occur. Our study provided the first evidence about interaction between T. harzianum and sulfide -mineralized hardpans as well as about its influence on gypsum genesis.